2020
DOI: 10.1186/s12985-020-01452-5
|View full text |Cite
|
Sign up to set email alerts
|

Rapid SARS-CoV-2 antigen detection assay in comparison with real-time RT-PCR assay for laboratory diagnosis of COVID-19 in Thailand

Abstract: Background The Coronavirus disease 2019 (COVID-19) pandemic continues to spread across the world. Hence, there is an urgent need for rapid, simple, and accurate tests to diagnose severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Performance characteristics of the rapid SARS-CoV-2 antigen detection test should be evaluated and compared with the gold standard real-time reverse transcription-polymerase chain reaction (RT-PCR) test for diagnosis of COVID-19 cases. Methods The rapid SARS-CoV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
237
4
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(273 citation statements)
references
References 11 publications
(13 reference statements)
8
237
4
7
Order By: Relevance
“…To date, several studies have evaluated the diagnostic performance of POCTs in real life, yielding conflicting data. [9][10][11][12][13][14][15][16][17][18][19][20][21] In general, the sensitivity ranged from 60.8% to 79.6%. [13][14][15][16][17][18] Occasionally, significantly high sensitivity (93.9% and 98.3%) has been reported.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…To date, several studies have evaluated the diagnostic performance of POCTs in real life, yielding conflicting data. [9][10][11][12][13][14][15][16][17][18][19][20][21] In general, the sensitivity ranged from 60.8% to 79.6%. [13][14][15][16][17][18] Occasionally, significantly high sensitivity (93.9% and 98.3%) has been reported.…”
Section: Discussionmentioning
confidence: 97%
“…[13][14][15][16][17][18] Occasionally, significantly high sensitivity (93.9% and 98.3%) has been reported. [19][20][21] Concerning the Panbio COVID-19 Ag Rapid test (Abbott), the manufacturer reported high sensitivity (93.3%; 95% CI, 83.8-98.2) in a highly endemic setting in Brazil, 22 but other independent cohort studies have not confirmed these data. In 257 symptomatic and asymptomatic patients enrolled at the Emergency Department and Primary Health Care Setting in Spain, the overall sensitivity was 73.3%, reaching 86.5% among patients having symptoms for less than seven days.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the detection of infective SARS-CoV-2 from upper respiratory specimens collected several days prior to symptom onset, lends further evidence for this to be considered to be a possible common feature of mild to asymptomatic COVID-19 infections. There are now several ways to detect the presence of SARS-CoV-2, both with PCR and antigen tests [ 26 , 27 ]. To mitigate the pandemic, early diagnosis is crucial to prevent further transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The manufacturer claims sensitivity 96.52% (95% CI 91.33-99.04%) and specificity 99.68% (95% CI 98.22 -99.99%) in the test package leaflet [18]. See Supplementary Material S1.3 for a further survey of 10 validation studies [20][21][22][23][24][25][26][27][28][29] with sensitivity median 78.1% and average 78.9%, and specificity median 99.4% and average 98.1%. The sample tested in the mass testing in Slovakia may significantly statistically differ from the validation studies samples.…”
Section: Methodsmentioning
confidence: 99%